2020
DOI: 10.1155/2020/6707239
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Steroid Use in Rhegmatogenous Retinal Detachment Associated with Choroidal Detachment after 23-Gauge Vitrectomy

Abstract: Background. Rhegmatogenous retinal detachment associated with choroidal detachment (RRDCD) is rare and the prognosis is poor. This retrospective study evaluated the effect of preoperative steroid on the clinical outcome of patients with RRDCD receiving 23-gauge pars plana vitrectomy (PPV). Methods. Sixty-six patients (67 eyes) with diagnosed RRDCD underwent 23-gauge PPV. The patients assigned to receive systemic or subtenon injection of preoperative steroids were considered Group A (35 eyes) and did not receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…However, Wu et al (2017) conducted a study that included 82 eyes of 82 patients with vitreous haemorrhage or opacity due to ocular trauma, retinal detachment or retinal vascular diseases including diabetic retinopathy (non selective cases) and they compared these results with the values 2 weeks after vitrectomy operation. The authors revealed that there was no improvement or reduction in postoperative visual acuity [14].…”
Section: Visual Acuity Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, Wu et al (2017) conducted a study that included 82 eyes of 82 patients with vitreous haemorrhage or opacity due to ocular trauma, retinal detachment or retinal vascular diseases including diabetic retinopathy (non selective cases) and they compared these results with the values 2 weeks after vitrectomy operation. The authors revealed that there was no improvement or reduction in postoperative visual acuity [14].…”
Section: Visual Acuity Resultsmentioning
confidence: 94%
“…Results were also in harmony with who showed that the preoperative visual electrophysiology was significantly correlated with the effectiveness of the operation. It is helpful in prognostic assessment of postoperative visual outcome [14].…”
Section: Erg Resultsmentioning
confidence: 99%
“…[ 23 ] A few studies have shown it to improve the final reattachment rates, while some studies reported no improvement in retinal reattachment rates or visual outcomes. [ 23 24 25 ] Nonetheless, almost two-third of the VRSI survey respondents preferred to start the patient on oral corticosteroids for at least 3–7 days before the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, this did not significantly improve the retinal reattachment rate or VA at 3 months postoperatively. Wu et al 12 found that systemic, sub-Tenon or subconjunctival injection of glucocorticoids 3 days before surgery did not have any effect on rates of reattachment after PPV. On the contrary, Gui et al 17 reported a 95% final surgical success rate for patients with RRD-CD of whom 81% used oral prednisolone and 19% received intravitreal triamcinolone preoperatively.…”
Section: Adjuvant Steroid Usementioning
confidence: 99%
“…2,8,9,11 Steroids have been administered through multiple routes in an attempt to improve surgical outcomes. 1,2,4,12–15 Various surgical approaches have been used including scleral buckle (SB), pars plana vitrectomy (PPV), pars plana lensectomy (PPL), and perfluorocarbon liquid (PFCL) tamponade. 15–18…”
mentioning
confidence: 99%